APPLICATION OF PROBIOTIC PRODUCT CONTAINING LACTOBACILLUS CASEI IMUNITASS IN CLINICAL PRACTICE - D.V. Usenko ("Paediatrician" Publishers LLC, 2007)
This article includes an overview of clinical research that study the efficiency of including into children's ration sour milk proc biotic product actimel (Danone, France), created on the basis of milk fermented with Lactobacillus bulgaricus and Streptococcus thermophilus, and enriched with culture of Lactobacillus casei DNC 114001 (commercial name L. casei imunitass). Key words: probiotic product, children, Lactobacillus casei DN 114001.